Keanekaragaman Mikroalga sebagai Bioindikator di Perairan Sungai - Mustika Elmi Dayana; Abdul Rahman Singkam; Dewi Jumiarni (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the diversity of microalgae and their relationship with water quality in the Air Lais River. The method used is a survey method. The results showed that there were 28 species of microalgae consisting of 7 divisions. The abundance of microalgae at the upstream station was 52 ind/ml, the middle station was 50 ind/ml and the downstream station was 115 ind/ml. The microalgae diversity index at each station was 2.2; 2.2; and 2.59, with a moderate level of diversity criteria. The microalgae dominance index was in the low dominance criteria, with the value of each station being 0.21; 0.20; and 0.14. In conclusion, the condition of the Air Lais River is still relatively clean and shows a normal tolerance range for microalgae life. Keywords: Diversity, Microalgae, Lais Water River